PERAN GURU DALAM PENGUATAN PENYELENGARAAN SEKOLAH RAMAH ANAK - Fauzan, Rizki; Mustaidah; Soejono (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This study aims to analyze the role of teachers in strengthening the implementation of Child-Friendly Schools (CFS) at SMA Negeri 1 Moga based on the Among System by Ki Hadjar Dewantara. The research employs a descriptive qualitative method, with data collected through observation, in-depth interviews, and documentation. The findings reveal that teachers play a crucial role in implementing the principles of "Ing Ngarso Sung Tuladha" (providing exemplary leadership), "Ing Madya Mangun Karsa" (encouraging innovation and participation), and "Tut Wuri Handayani" (offering support and motivation). Teachers act as role models, facilitators, motivators, and mentors, fostering a safe, comfortable, and inclusive learning environment for students. The study concludes that the consistent application of the Among System significantly enhances the success of CFS, particularly in strengthening moral values, encouraging active student participation, and promoting character-based learning. The study implies that continuous training and socialization are essential for teachers to fully understand and effectively implement the values of the Among System in CFS programs.